Perianal vesicular eruption with centrifugal spreading. - Scanni, G. (European Journal of Pediatric Dermatology, 2007)
When considering the onset (pseudomucosa) and the non centripetal spreading, probably it was not so easy to diagnose varicella at the first visit.